Histological observations and its variations in appendix at different stages of life - George, Jessy Rose (International Journal of Research in Medical Sciences, 2017)
Background: It was reported that the appendix is a tough soldier against infection, especially in people who have been exposed to some types of radiation. Early in a child’s life the appendix is relatively larger than it is in an adult which creates confusion. Hence, it is need to explore the histological details at different stages of life before the functional details. Methods: The present study was conducted after an institutional ethical clearance. Fifty six human appendices were collected for histological study. The fixed specimens were subjected to the process of paraffinisation and processed for staining with routine haematoxylin and eosin methods, Gamori’s methenamine silver method and AB – PAS staining method using standard procedures. Results: Histological features during the foetal period and first decade lumen of appendix appeared large and three cornered or irregular with comparatively thin wall, in second and third decades lumen became very narrow to almost occluded, in the fourth and fifth decades lumen appeared wide as the wall thinned out. In the sixth decade appendix almost appeared oval in shape and the lumen was almost obliterated in seventh and eighth decades. Conclusions: The thickness of the mucosa kept increasing in the second decade onwards and in the later decades both lymphatic tissues and crypts were markedly reduced and by eighth decade these features were not present at all.